1994
DOI: 10.1207/s15327752jpa6201_7
|View full text |Cite
|
Sign up to set email alerts
|

Confounding Factors in the Measurement of Depression in HIV

Abstract: Our study investigates the nature of elevated depression scores on the MMPI-168 in human-immunodeficiency-virus- (HIV-)infected individuals. Comparison of MMPI scales, factor scores, and individual depression item endorsement rates were made between three groups of homosexual/bisexual men: asymptomatic HIV-1 seropositives (n = 156), symptomatic HIV-1 seropositives (n = 156), and a comparison group of HIV-1 seronegatives (n = 117). Elevated scores were found on the MMPI depression scale for all three groups, wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 33 publications
1
18
0
Order By: Relevance
“…However, the results are not very consistent, some studies showing that the presence of depressive symptoms is associated with poorer neuropsychological performance, 12–14 whereas other authors did not find this relationship 15–21 . Some authors have suggested that this lack of agreement may be related to other factors such as the instruments used to measure mood, 12,22–24 or the stage of infection of the patients at the time of evaluation 25–27 …”
Section: Introductionmentioning
confidence: 94%
“…However, the results are not very consistent, some studies showing that the presence of depressive symptoms is associated with poorer neuropsychological performance, 12–14 whereas other authors did not find this relationship 15–21 . Some authors have suggested that this lack of agreement may be related to other factors such as the instruments used to measure mood, 12,22–24 or the stage of infection of the patients at the time of evaluation 25–27 …”
Section: Introductionmentioning
confidence: 94%
“…Internal consistency for our total sample was good at 0.91. The CES-D is an appropriate measure of depression in an HIV-positive population, because it is less prone to inflation due to somatic and neurological symptoms endorsed by HIV-positive individuals than other depression measures (Drebing et al 1994;Radloff 1977).…”
Section: Depressionmentioning
confidence: 99%
“…A review of the literature as well as our initial bivariate analyses uncovered the AIDS Behav (2010) 14:390-400 393 importance of controlling for symptom load (e.g. Drebing et al 1994), gender, age, years since HIV diagnosis, and ethnicity in HIV-positive individuals, to protect the model from a possible confound.…”
Section: Data Analysesmentioning
confidence: 99%
“…1 In the pre-highly active antiretroviral therapy (HAART) era, depressive symptoms and other mood problems were shown to be substantial problems for patients with HIV/AIDS. [2][3][4][5] Although there is some evidence to indicate that with the advent of HAART and improved long-term prognosis, the rates of mood disorders may have decreased, those findings have been inconsistent, and mood disorders continue to be a substantial problem in both women and men with HIV. [6][7][8][9][10][11][12] In a recent investigation of veterans with HIV, the majority of patients reported having significant levels of depressive symptoms.…”
mentioning
confidence: 99%